The Effect Of The 4Ps Marketing Mix On Purchasing Decisions At The Dometex Bandung Fabric Store - Aulia, Siti Zahwa; Koeswandi , Tika; Rachmani , Nizza Nadya (The Future of Education Journal, 2025)
In an era of increasingly fierce business competition, especially for micro, small, and medium enterprises (MSMEs) such as fabric stores in Bandung, the right marketing strategy is key to attracting and retaining customers. The 4Ps marketing mix, which includes quality products, affordable prices, easy distribution, and attractive promotions, is the main foundation for businesses to influence customer purchasing decisions. Dometex Bandung fabric store, as one of the MSMEs in the Tamim area that offers a variety of fabrics by the meter, systematically implements the 4Ps to get closer to consumers. This study aims to examine the effect of the 4Ps marketing mix on consumer purchasing decisions, focusing on how these elements shape perceptions and shopping behavior amid the dynamics of the textile market. The method used is quantitative with a descriptive-verificative approach, where data is collected through questionnaires distributed to the entire population of 139 respondents using purposive non-probability sampling with a saturated sample type. Data analysis is carried out with instrument testing, classical assumption testing, and hypothesis testing using SPSS. The results show that the 4Ps marketing mix has a strong and significant influence on consumer purchasing decisions, especially in terms of promotion, which has a significant and dominant influence on purchasing decisions. The research model has been proven to be feasible and capable of strongly explaining variables through high determination coefficient values. These findings confirm that the right promotional strategy can significantly increase purchasing decisions.